A Research Agenda for Urban Biodiversity in the Global Extinction Crisis. (9th December 2020) - Knapp, Sonja; Aronson, Myla F J; Carpenter, Ela; Herrera-Montes, Adriana; Jung, Kirsten; Kotze, D Johan; La Sorte, Frank A; Lepczyk, Christopher A; MacGregor-Fors, Ian; MacIvor, J Scott; Moretti, Marco; Nilon, Charles H; et al.
Abstract: Rapid urbanization and the global loss of biodiversity necessitate the development of a research agenda that addresses knowledge gaps in urban ecology that will inform policy, management, and conservation. To advance this goal, we present six topics to pursue in urban biodiversity research: the socioeconomic and social–ecological drivers of biodiversity loss versus gain of biodiversity; the response of biodiversity to technological change; biodiversity–ecosystem service relationships; urban areas as refugia for biodiversity; spatiotemporal dynamics of species, community changes, and underlying processes; and ecological networks. We discuss overarching considerations and offer a set of questions to inspire and support urban biodiversity research. In parallel, we advocate for communication and collaboration across many fields and disciplines in order to build capacity for urban biodiversity research, education, and practice. Taken together we note that urban areas will play an important role in addressing the global extinction crisis.